"I deserve a treat": Exercise motivation as a predictor of post-exercise dietary licensing beliefs and implicit associations toward unhealthy snacks. (September 2017) - West, Jessica; Guelfi, Kym J.; Dimmock, James A.; Jackson, Ben
Abstract: Objective: To explore whether exercise motivation predicted two of the potential mechanisms that may explain why individuals engage in unhealthy compensatory snack consumption following exercise; specifically (a) post-exercise conscious licensing beliefs, and (b) post-exercise implicit attitudes toward unhealthy snacks. Design: Observational study. Method: One hundred and nineteen healthy participants completed a 40-min session of moderate intensity stationary cycling, and subsequently completed measures of explicit licensing and implicit associations toward unhealthy snack foods and drinks. Results: Individuals driven by more controlled (relative to autonomous) forms of exercise motivation reported greater compensatory licensing beliefs ( Est = −0.08, p < 0.001) even after accounting for a number of relevant covariates. No significant relationship emerged between exercise motivation and implicit associations toward unhealthy snacks ( Est = 0.12, p = 0.81). Conclusion: The findings demonstrate that exercise motivation may predict conscious licensing beliefs toward unhealthy snack foods and drinks post-exercise. Understanding the modifiable factors – such as exercise motivation – that predict post-exercise dietary beliefs is important for supporting individuals' weight loss and health goals. Highlights: Exercise motivation may predict mechanisms underlying post-exercise snacking. Reflective and impulsive responses were recorded after a 40-min exercise session. Controlled motivation predicted greater post-exercise licensing beliefs regarding unhealthy snacks. The first study to link exercise motivation to mechanisms underlying post-exercise snacking.